RELATIONSHIP BETWEEN MENOPAUSE AND WOUND HEALING PROCESS AFTER TOOTH EXTRACTION IN DENTAL CLINIC UNIVERSITY WIJAYA KUSUMA SURABAYA - Parmasari, Wahyuni Dyah; Theodora, Theodora; Willianti, Enny (Jurnal Ilmiah Kedokteran Wijaya Kusuma, 2016)
Backgrounds : In medicine faculty specially in oral health university of Wijaya Kusuma Surabaya, extracting is the most common cases in clinic. As we know geriatry patients needs this treats too. The newest reports explain that estrogenes affected production of collaagens. Collagens are needed for asselarate wound healing. Menopause process decrease production of estrogen, so it can be influance for collagens output product.Purpose : This experimental to discribe the connection between menopause with clinical wound Â healing process after tooth extraction at the Poli Gigi Universitas Wijaya Kusuma Surabaya.Â Methodes : This experimental use wound healing scale use parameters Tumor (swelling), Rubor (hyperemia) and Dolor (pain) Results : In this study used 20 patients divided two groups, menopause and non menopause group. There was a significant difference between menopause group and non menopause group in the third day and the fifth day after tooth extracted. For geriatry patients need dental care, specially tooth extraction. The complication in this age is delayed wound healing. For woman cases has many degeneration problems, one of this is because oldery ages woman has fisiology prosess menopause periode. Menopause is a regeneration process makes ovarium stops producting ovum. It was effected for maturation ovum and distrubing production of collagens. Collagens have main factors for wound healing process. In this articles, writer tried to connected the relations delayed wound healing in woman that have been in menopause period in case extracted teeth. Conclusion : There is a significant different between wound healing menopause and non menopause. The menopause the process wound healing takes more longer than non menopause.